Burdens of Family Caregivers of Stroke Patients: An Integrative Literature Review - Mercado, Myrna A (Health Notions, 2018)
Stroke is primarily one of the chronic diseases resulting to varying physical disabilities and cognitive changes that need assistance from the unprepared informal family caregivers. The objective of this article is to explore the burdens of family caregivers of stroke patients. This integrative review of literature from the year 2013 to 2017 using CINAHL, Medline, ProQuest and Google Scholar databases resulted to inclusion of six quantitative and two qualitative studies. Results revealed varying degrees of physical, emotional, social and financial burdens that has mostly affected the caregiversâ quality of life specifically the physical domain due to various patient and caregiver related factors. Problem solving strategies to cope the consequences of burdens was commonly used. In conclusion, burdens can be curtailed if caregiversâ needs will be targeted by providing stroke-related health information, training to develop care-taking skills and technique along with provision of financial, social and emotional support.